1996
DOI: 10.1080/02652039609374451
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A in table wine and grape‐juice: Occurrence and risk assessment∗

Abstract: The concentrations of ochratoxin A (OA) and C (ethyl ester of OA, OC) have been measured in table wine from the Swiss retail market. The overall median concentrations of OA in white, rose and red table wine were (number of samples; range) < 3 pg/ml (24; < 3-178 pg/ml), 19 pg/ml (15; < 3-123 pg/ml) and 13 pg/ml (79; < 3-388 pg/ml)), respectively. For dessert wines (Malaga, Marsala) a median of 337 pg/ml (5; 44-451 pg/ml) resulted. Concentrations of OC were about 10% of those of OA. OA has been detected in red g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
307
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 445 publications
(333 citation statements)
references
References 7 publications
14
307
2
4
Order By: Relevance
“…This second hypothesis is supported by the alcoholic and acidic nature of wine that permits transformation of the carboxylic acid into an ethanolic ester [19]. OTC is rapidly hydrolyzed to OTA after oral or intravenous administration, acting as a pro-OTA product [20].…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This second hypothesis is supported by the alcoholic and acidic nature of wine that permits transformation of the carboxylic acid into an ethanolic ester [19]. OTC is rapidly hydrolyzed to OTA after oral or intravenous administration, acting as a pro-OTA product [20].…”
mentioning
confidence: 91%
“…The simultaneous appearance of OTA and OTC in wine was first described by Zimmerli and Dick in 1996 [19], although since then, no more studies have been carried out on the same topic. These authors indicated that in chromatograms of wine samples with OTA levels superior to 0.050 µg L -1 , an additional peak was detected and its retention time corresponded to that of the ethyl ester.…”
mentioning
confidence: 99%
“…OTA levels in juices were lower than 2ng mL -1 in other studies cited in table 1, in which the occurrence of this mycotoxin was evaluated, including samples from Brazil (ROSA et al, 2004;SHUNDO et al, 2006), China (CAO et al, 2013, Spain (BELLI et al, 2004), Malaysia (LEE et al, 2012 and Switzerland (ZIMMERLI & DICK, 1996). In these cases, the OTA exposure through consumption of juice has not represented a health risk, since the estimated exposure to this toxin were lower than the value established as PTWI by JECFA (ZIMMERLI & DICK, 1996;ROSA et al, 2004;BELLI et al, 2004;SHUNDO et al, 2006;LEE et al, 2012;CAO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the OTA exposure through consumption of juice has not represented a health risk, since the estimated exposure to this toxin were lower than the value established as PTWI by JECFA (ZIMMERLI & DICK, 1996;ROSA et al, 2004;BELLI et al, 2004;SHUNDO et al, 2006;LEE et al, 2012;CAO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation